Distribution of repetitive DNA sequences in eubacteria and application to fingerprinting of bacterial genomes. - Versalovic, J (1991)
Dispersed repetitive DNA sequences have been described recently in eubacteria. To assess the distribution and evolutionary conservation of two distinct prokaryotic repetitive elements, consensus oligonucleotides were used in polymerase chain reaction [PCR] amplification and slot blot hybridization experiments with genomic DNA from diverse eubacterial species. Oligonucleotides matching Repetitive Extragenic Palindromic [REP] elements and Enterobacterial Repetitive Intergenic Consensus [ERIC] sequences were synthesized and tested as opposing PCR primers in the amplification of eubacterial genomic DNA. REP and ERIC consensus oligonucleotides produced clearly resolvable bands by agarose gel electrophoresis following PCR amplification. These band patterns provided unambiguous DNA fingerprints of different eubacterial species and strains. Both REP and ERIC probes hybridized preferentially to genomic DNA from Gram-negative enteric bacteria and related species. Widespread distribution of these repetitive DNA elements in the genomes of various microorganisms should enable rapid identification of bacterial species and strains, and be useful for the analysis of prokaryotic genomes.